Patterns of constitutive and IFN-γ inducible expression of HLA class II molecules in human melanoma cell lines - Rodríguez, Teresa; Méndez, Roman; Schadendorf, Dirk (Immunogenetics, 2007)
Major histocompatibility complex (MHC) class II proteins (HLA-DR, HLA-DP and HLA-DQ) play a fundamental role in the regulation of the immune response. The level of expression of human leukocyte antigen (HLA) class II antigens is regulated by interferon-γ (IFN-γ) and depends on the status of class II trans-activator protein (CIITA), a co-activator of the MHC class II gene promoter. In this study, we measured levels of constitutive and IFN-γ-induced expression of MHC class II molecules, analysed the expression of CIITA and investigated the association between MHC class II transactivator polymorphism and expression of different MHC class II molecules in a large panel of melanoma cell lines obtained from the European Searchable Tumour Cell Line Database. Many cell lines showed no constitutive expression of HLA-DP, HLA-DQ and HLA-DR and no IFN-γ-induced increase in HLA class II surface expression. However, in some cases, IFN-γ treatment led to enhanced surface expression of HLA-DP and HLA-DR. HLA-DQ was less frequently expressed under basal conditions and was less frequently induced by IFN-γ. In these melanoma cell lines, constitutive surface expression of HLA-DR and HLA-DP was higher than that of HLA-DQ. In addition, high constitutive level of cell surface expression of HLA-DR was correlated with lower inducibility of this expression by IFN-γ. Finally, substitution A→G in the 5′ flanking region of CIITA promoter type III was associated with higher expression of constitutive HLA-DR (p<0.005). This study yielded a panel of melanoma cell lines with different patterns of constitutive and IFN-γ-induced expression of HLA class II that can be used in future studies of the mechanisms of regulation of HLA class II expression.